Challenges in experimental investigations of Paracoccus denitrificans activities in salt-bearing porous media - J. Qajar; S. E. Celik; A. Reyes Amezaga; S. Godts; S. Godts; L. Schröer; A. Raoof; V. Cnudde; V. Cnudde (Advances in Geosciences)
Salt weathering, driven by the crystallization of saline solutions within sedimentary rocks, leads to significant material degradation. Key factors influencing this process include salt type, concentration, moisture levels, temperature fluctuations, and pore structure. Environmental conditions and microbial activity further impact weathering, either mitigating or exacerbating its effects. Microorganisms contribute to biological weathering but may also enhance rock properties through biofilm formation or biocementation. Laboratory techniques such as rock testing and micromodel experiments face challenges in replicating complex interactions between microorganisms and salt-bearing porous materials. In this study, we investigated the activity of Paracoccus denitrificans in saline solutions through experiments conducted on Petri dishes, glass slides and micromodels. Key challenges included replicating controlled conditions, managing contamination, and maintaining strict environmental controls. The results highlighted significant challenges in interpreting bacterial activity within salt-bearing systems, particularly due to contamination risks and difficulties in maintaining precise experimental conditions. Additionally, experimental setups, such as fluid actuation using laser light beams, were found to introduce further complexities. This research provided recommendations and emphasized the critical need for refined methodologies to enhance accuracy and reliability in future studies.